1992
DOI: 10.1152/jappl.1992.72.3.1024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gas and liquid ventilation: clinical, physiological, and histological correlates

Abstract: To differentiate the effects of gas and liquid ventilation on cardiopulmonary function during early development, we compared the clinical, physiological, and histological profiles of gas- and liquid-ventilated preterm lambs (n = 16; 108-116 days gestation). Immediately after cesarean section delivery, ventilation commenced using gas delivered by a volume ventilator (n = 9) or liquid perfluorochemical (n = 7) delivered by a mechanically assisted liquid ventilation system. Pulmonary gas exchange, acid-base statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(106 citation statements)
references
References 0 publications
3
103
0
Order By: Relevance
“…A few studies reported hemodynamic compromise during total liquid ventilation. The authors of these studies attributed this result to the filling of the lung with high-density PFCs [2,3]. The observed hemodynamic compromise in these total liquid ventilation studies is speculated to result from pulmonary vascular compression, which is caused by an increase in the alveolar hydrostatic pressure gradient [9], and/or through an impairment of CO via a decrease in right ventricular preload combined with an increase in right ventricular afterload [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies reported hemodynamic compromise during total liquid ventilation. The authors of these studies attributed this result to the filling of the lung with high-density PFCs [2,3]. The observed hemodynamic compromise in these total liquid ventilation studies is speculated to result from pulmonary vascular compression, which is caused by an increase in the alveolar hydrostatic pressure gradient [9], and/or through an impairment of CO via a decrease in right ventricular preload combined with an increase in right ventricular afterload [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since then PFCs have been investigated extensively as an alternative means of respiratory support, and PFCs oxygenated outside the body have been used in the treatment of acute respiratory failure [2,3]. In 1991 Fuhrman et al [4] demonstrated the feasibility of applying liquid ventilation in healthy animals without the need for a specialized liquid breathing system.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has also been shown to improve gas exchange and lung function in animal models of respiratory distress. [8][9][10][11] In 1991, Fuhrman et al 12 introduced the technique of using functional residual capacity (FRC) volumes of PFC with conventional gas ventilation -PFC associated gas exchange (PAGE). This technique has become known as partial liquid ventilation (PLV) and it is this technique which has the most promise for practical clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest newer technologies, such as partial liquid ventilation (PLV) and high-frequency oscillatory ventilation (HFOV) that can reduce the severity of lung injury in experimental and clinical settings (1)(2)(3)(4)(5)(6)(7)(8)(9). HFOV has been known to be effective rescue modality in patients with a significant impairment of gas exchange (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%